A Note on the Laplacian Energy of the Power Graph of a Finite Cyclic Group - VARLIOĞLU, NURŞAH MUTLU; Büyükköse, Şerife (Sakarya Üniversitesi Fen Bilimleri Enstitüsü, 2024)
In this study, the Laplacian matrix concept for the power graph of a finite cyclic group is redefined by considering the block matrix structure. Then, with the help of the eigenvalues of the Laplacian matrix in question, the concept of Laplacian energy for the power graphs of finite cyclic groups was defined and introduced into the literature. In addition, boundary studies were carried out for the Laplacian energy in question using the concepts the trace of a matrix, the Cauchy-Schwarz inequality, the relationship between the arithmetic mean and geometric mean, and determinant. Later, various results were obtained for the Laplacian energy in question for cases where the order of a cyclic group is the positive integer power of a prime.
Keywords: Cyclic Group; Laplacian Matrix; Laplacian Energy; Bound